(3/4)y-(1/4)=(5/4)y+(1/8)

Simple and best practice solution for (3/4)y-(1/4)=(5/4)y+(1/8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3/4)y-(1/4)=(5/4)y+(1/8) equation:


(3/4)y-(1/4)=(5/4)y+(1/8)

We simplify the equation to the form, which is simple to understand
(3/4)y-(1/4)=(5/4)y+(1/8)

Reorder the terms in parentheses
( + 0.75y)-( + 0.25)=(+1.25)*y+( + 0.125)

Remove unnecessary parentheses
+ 0.75y-( + 0.25)=(+1.25)*y+( + 0.125)

Remove unnecessary parentheses
+ 0.75y-0.25=(+1.25)*y+( + 0.125)

Reorder the terms in parentheses
+ 0.75y-0.25=(+1.25y)+( + 0.125)

Remove unnecessary parentheses
+ 0.75y-0.25=+1.25y+( + 0.125)

Remove unnecessary parentheses
+ 0.75y-0.25=+1.25y + 0.125

We move all terms containing y to the left and all other terms to the right.
+ 0.75y-1.25y=0.125 + 0.25

We simplify left and right side of the equation.
-0.5y=0.375

We divide both sides of the equation by -0.5 to get y.
y=-0.75

See similar equations:

| 4(p-1)=5p+3p-8(2p+2) | | 4x+76x=37 | | log^3(14x-3)=log^3(6x+5) | | -5x-12=-8x | | 2x+4=-12x+14 | | 8a+6=76 | | -4x-3=-4x+4 | | x^2+50x=21279 | | (5x^2+6x+12)=0 | | Letq=180 | | a=2pir^2h | | x^2+50x=6600 | | -3x+8=-3x | | 6x+4=-2+28 | | 8y-3=3y-2+4y | | 3(4x+5)=7(x-4)+17 | | (2/3)x+(1/6)=(-5/6)x+(5/3) | | 4x+12=3(x+4) | | -56=-4x-2(-7x-2) | | 7(6+x)=6(2-x) | | 328=8(6a+5) | | -5x=-x-12 | | 10x^2-66x+72=0 | | -4x+83=-12x-125 | | 0.5y-2=-.25 | | 10+5(x-2)=4x+1 | | -29=5x-2(3x+10) | | 36x+24=10(x+2+2x) | | 7h-14=42 | | -4-3=0.4x-2y | | -4(x+4)=2(x-10) | | 5g+15=42 |

Equations solver categories